The contribution of grit, emotions and personal bests to foreign language learning - Khajavy, Gholam Hassan; Aghaee, Elham (Journal of multilingual and multicultural development, 2024)
This study aimed to examine grit and its components (i.e. perseverance of effort and consistency of interest) in the foreign language (L2) classrooms by investigating its relations to personal best goals, L2 emotions (i.e. enjoyment and anxiety) and L2 achievement. We further examined whether grit could predict L2 achievement when other constructs are included in the analyses. For this purpose, a total of 226 participants who were studying English in a language institute completed the questionnaire. When grit was the only predictor of L2 achievement, results indicated that only perseverance of effort could significantly predict L2 achievement. However, when other predictors were included in the analyses, neither of grit components could predict L2 achievement. We further found that both grit components predicted L2 anxiety, while only perseverance of effort predicted L2 enjoyment and personal best goals. Finally, we found that perseverance of effort was indirectly related to L2 achievement through personal bests. These findings show the problematic role of consistency of interest in predicting L2 achievement reflecting the arguments made in the field of education. Results of the study provide us with important findings concerning the mechanism underlying the relations between grit and L2 achievement and how this relation might be mediated through personal best goals.